2014
DOI: 10.17761/ijyt.24.1.5003007856u32q52
|View full text |Cite
|
Sign up to set email alerts
|

Flexibility of the Elderly after One-Year Practice of Yoga and Calisthenics

Abstract: Flexibility training responses to distinct stretching techniques are not well defined, especially in the elderly. This study compared the flexibility of elderly individuals before and after having practiced hatha yoga and calisthenics for 1 year (52 weeks), at least 3 times/week. Sixty-six subjects (12 men) measured and assigned to 3 groups: control (n = 24, age = 67.7±6.9 years), hatha yoga (n = 22, age = 61.2±4.8 years), and calisthenics (n = 20, age = 69.0±5.8 years). The maximal range of passive motion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 3 publications
0
8
0
2
Order By: Relevance
“…Resistance training can counteract sarcopenia (36), which naturally occurs with aging (37), by increasing muscle mass, strength (29), and stability (9) and thus decrease walking cost (14). Stretching exercises improve flexibility, joint range of motion, and proprioception with consequent effects on balance and stability (11,19), which might result in reduced walking cost. Endurance training aims at improving cardiovascular conditioning and results in increased maximal oxygen uptake as well as reduced recovery time (13,16).…”
mentioning
confidence: 99%
“…Resistance training can counteract sarcopenia (36), which naturally occurs with aging (37), by increasing muscle mass, strength (29), and stability (9) and thus decrease walking cost (14). Stretching exercises improve flexibility, joint range of motion, and proprioception with consequent effects on balance and stability (11,19), which might result in reduced walking cost. Endurance training aims at improving cardiovascular conditioning and results in increased maximal oxygen uptake as well as reduced recovery time (13,16).…”
mentioning
confidence: 99%
“…Research from Brisbon & Lowery, 2009; Wyshake & Sklar 2009 shown that yoga can increase happiness, reduce stress anxiety and depression. This thing is also strengthen by the research result of Farinatti et al (2014), which is stated that flexibility in ankle, knee, hip, back bone, wrist, elbow and shoulder also total flexibility (Flexindex) showing there is significance enhancement after doing yoga training. Nagai (1993: 88), stated that the stiffness of the body can be erased by doing mako training intensively.…”
Section: Discussionmentioning
confidence: 60%
“…One of the studies (Farinatti et al, 2014) on Yoga was compared to many other physical workout groups, including aerobics and stretching exercise. In a research study on calisthenics, the author compares a Yoga group with a calisthenics group, where they conducted three sessions a week.…”
Section: Discussionmentioning
confidence: 99%
“…However, this exploratory study is an attempt to include all the significant domains of wellness through the IWS survey and highlight the various effects of Yoga practice through GYP. One of the studies (Farinatti et al, 2014) on Yoga was compared to many other physical workout groups, including aerobics and stretching exercise. In a research study on calisthenics, the author compares a Yoga group with a calisthenics group, where they conducted three sessions a week.…”
Section: Discussionmentioning
confidence: 99%